Ensino e identidades: um estudo sobre as mulheres negras na escola - Jacob, Hemanuelle Di Lara Siqueira (2017)
The law 10.639/03 states that the history and African culture teaching as well as Afrobrazilian be mandatory in elementary and high school establishments, be them public or private. This law states that these subjects shall be managed in all the school curriculum context. However, what is noticed is that the Afro culture debate is up to one or other subject. This fragmentation does not create any satisfactory effect, since the ethnic-racial prejudice is a historical and social construction that reaches beyond all the disciplinary and school contexts. Therefore, the main objective of this research was to elaborate a didactic sequence for the Physical Education subject with the theme “The Black Woman in Soccer”, towards the human formation and the combat against various types of violence and discrimination practiced against the black population, and specifically black women. A case study was carried out, of exploring characteristic and qualitative approach with the main methodology of focusing groups with students and female workers of a municipal school in Goiania. Authors such as Hall (2003, 2005), Silva (2000, 2010), Castells (2006) and Giddens (2003) gave us support with the identity debate. On the other hand Bourdieu (1998), Saviani (2008) e Coletivo de Autores (2006), were our references regarding the question of school and the role of a critical and transforming education. And to analyze the gender and power relations, we started from the considerations of Scott (1995), Gomes (2002, 2005, 2012) and Haraway (2005). We identified initially that there is still an invisible barrier that stigmatizes and excludes black women from the job market and in other aspects of life. The data that supports this reality can be found in the last Women Socioeconomic Annual Report (2015), carried out by the Secretariat of Policies for Women, that shows the socioeconomic and demographic disparities in the ethnic-racial configurations, of gender and class in Brazil.